Legal documents from the Judean desert the impact of the Sharīʻa on Bedouin customary law - Layish, Aharon, 1933- (Studies in Islamic Law and Society, 2011)
This volume presents annotated English translations of 74 awards handed down by tribal arbitrators and other legal documents obtained from the Bedouin of the Judean Desert. The documents address such legal issues as blood and sexual offenses, family disputes, inheritance, private transactions in land and water rights, tribal boundaries, contracts and obligations. The documents, some of which date back to the 19th century, provide vital information on the process of Islamization of the tribal customary law in the precinct of the tribal judge. The facsimile reproductions of the manuscripts are included, rendering direct access to the original documents. The study is intended for students of Islamic law, of customary law and of comparative law, and historians interested in the legal, social and economic history of modern Palestine and Jordan. A linguistic essay, by Dr. Mūsā Shawārbah, based on the Bedouin documents, appears at the end of the study.